Polishing composition and manufacturing method for magnetic disc substrate
The polishing composition with a specific water-soluble polymer and abrasive grains addresses the issue of increased polishing resistance and deformation in Ni-P substrate polishing, achieving improved surface quality and processability.
Patent Information
- Application Number
- JP2024121119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-07-26
- Publication Date
- 2025-04-10
AI Technical Summary
The thinning of Ni-P substrates leads to decreased rigidity of carriers used in polishing, causing deformation and increased polishing resistance, which results in scratches on the polishing pad and reduced surface quality of the substrate.
A polishing composition comprising abrasive grains, an acid, an oxidizing agent, a water-soluble polymer (A) with specific monomer units, and water is used to reduce polishing resistance and improve processability on Ni-P substrates.
The proposed solution effectively reduces polishing resistance and improves processability, leading to enhanced surface quality and reduced deformation of the carrier during the polishing of Ni-P substrates.
Smart Images

Figure 2025060404000001 
Figure 2025060404000002 
Figure 2025060404000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition and a method for producing a magnetic disk substrate. [Background technology]
[0002] Conventionally, the manufacturing process of a substrate that requires a highly accurate surface includes a step of polishing the substrate to be polished, which is the raw material of the substrate, using a polishing liquid. For example, in the manufacture of a nickel-phosphorus-plated magnetic disk substrate (hereinafter also referred to as Ni-P substrate), polishing that places emphasis on polishing efficiency (primary polishing) and final polishing (finish polishing) that is performed to achieve the surface accuracy of the final product are generally performed. Patent Document 1 is an example of a technical document related to a polishing composition used for polishing Ni-P substrates. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-155732 A Summary of the Invention [Problem to be solved by the invention]
[0004] Polishing of a Ni-P substrate is usually performed by pressing a polishing pad against the object to be polished (Ni-P substrate) held by a carrier, supplying a polishing liquid between the object to be polished and the polishing pad, and relatively moving (e.g., rotating) the object to be polished and the polishing pad along the surface direction of the object to be polished. The carrier holds the side (end face) of the substrate to be polished during polishing. Although not particularly limited, the carrier is usually a member that is thinner than the object to be polished and has a holding hole called a hole, and the object to be polished is placed in the holding hole. During polishing, the carrier receives a reaction force (a force that moves the object to be polished in the surface direction) against the action of the polishing pad on the object to be polished at the side of the holding hole.
[0005] Incidentally, in recent years, the carrier has become thinner as the Ni-P substrate becomes thinner. When the carrier becomes thinner, its rigidity decreases and it becomes more likely to deform when subjected to a force. When the carrier deforms, for example, a part of the deformed carrier may pierce the polishing pad and act on the polishing pad, which may cause scratches on the polishing pad. Such scratches on the polishing pad affect the surface quality of the object to be polished, and therefore require replacement of the polishing pad, which is undesirable.
[0006] The reaction force acting on the carrier increases in proportion to the increase in the polishing resistance (frictional force) acting between the polishing pad and the object to be polished. For example, in finish polishing, which requires high surface accuracy, the polishing pad and the substrate are easily attached to each other due to the fineness of abrasive grains such as silica, which tends to increase the frictional force between the polishing pad and the object to be polished, and the load on the carrier also tends to increase. In such polishing, if the polishing resistance acting between the object to be polished and the polishing pad during polishing can be reduced, the load on the carrier can be alleviated, and deformation of the carrier can be prevented or suppressed, thereby preventing pad scratches.
[0007] In addition, in polishing Ni-P substrates, improvement of processing power is required not only in primary polishing but also in finish polishing, and it is desirable to reduce the above-mentioned polishing resistance while maintaining sufficient processing power. For example, in finish polishing, silica particles such as colloidal silica are used as abrasive grains to obtain high surface accuracy, but in polishing using silica particles, it tends to be difficult to obtain processing power, so it is particularly meaningful if both improvement of processability and reduction of polishing resistance can be achieved.
[0008] The present invention has been made in view of the above circumstances, and aims to provide a polishing composition that can be used for polishing Ni-P substrates and can simultaneously reduce polishing resistance and improve processability. Another related aim is to provide a method for manufacturing a magnetic disk substrate using such a polishing composition. [Means for solving the problem]
[0009] According to the present specification, there is provided a polishing composition used for polishing a magnetic disk substrate having a nickel phosphorus plating layer. This polishing composition contains abrasive grains, an acid, an oxidizing agent, a water-soluble polymer (A), and water. The water-soluble polymer (A) is composed of one or more monomer units (a) having an SP value of 12.5 or more, and one or more monomer units (b) having an SP value of less than 12.5. The SP value of the water-soluble polymer (A) is in the range of 11 to 17. With the above polishing composition, it is possible to achieve both reduced polishing resistance and improved processability in polishing a Ni-P substrate.
[0010] In some embodiments, the water-soluble polymer (A) is a copolymer of two or more vinyl monomers. The vinyl monomers include at least one monomer selected from structures I and II. [ka] Here, in the above structure I, R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a linear or branched alkyl or alkenyl group having 10 or less carbon atoms, or R2 and R3 are bonded to each other to form a cyclic structure. By using the water-soluble polymer (A) having the above chemical structure, it is possible to preferably achieve both reduced polishing resistance and improved processability.
[0011] In some embodiments, the vinyl monomer preferably further comprises a carboxylic acid group-containing monomer. By using the water-soluble polymer (A) having the above chemical structure, it is possible to preferably achieve both reduced polishing resistance and improved processability.
[0012] In some embodiments, the polishing composition contains silica particles as the abrasive grains. The effects of the technology disclosed herein can be effectively exhibited in embodiments using silica as the abrasive grains.
[0013] In some embodiments, the silica particles have an average silanol group density of 3.0 / nm 2 By using silica particles having an average silanol group density of a predetermined value or less as an abrasive, it is possible to improve processability.
[0014] In some embodiments, the abrasive grains have an average aspect ratio of 1.0 or more and 1.3 or less based on transmission electron microscope observation. By making the average aspect ratio of the abrasive grains 1.0 or more and 1.3 or less, the abrasive grains are easy to roll during polishing, and the polishing resistance is reduced, so that the processing is stable and it is easy to achieve high surface quality after polishing. The polishing composition having such a configuration can be preferably used in a polishing process (for example, a finish polishing process) that requires high surface quality after polishing.
[0015] In some embodiments, the weight average molecular weight of the water-soluble polymer (A) is 8,000 or more and 50,000 or less. By using a water-soluble polymer (A) having a weight average molecular weight within the above range, it is possible to preferably achieve both reduced polishing resistance and improved processability.
[0016] In some embodiments, the polishing composition has a pH within the range of 1 to 4. In such a pH environment, the effects of the technology disclosed herein are preferably realized.
[0017] In some embodiments, the polishing composition is used in the final polishing step.The polishing composition disclosed herein is particularly suitable for the final polishing that requires high surface quality after polishing.The polishing composition disclosed herein is used in the final polishing of Ni-P substrate, and can preferably achieve both reduction of polishing resistance and improvement of processability.
[0018] This specification also provides a method for producing a magnetic disk substrate. This method includes a step of polishing a substrate to be polished with any one of the polishing compositions disclosed herein. This method allows efficient production of a magnetic disk substrate (Ni-P substrate). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Preferred embodiments of the present invention will be described below. Note that matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field.
[0020] <Polishing composition> (Abrasive grain) The polishing composition disclosed herein contains abrasive grains. The abrasive grains have the function of mechanically polishing the surface of the Ni-P substrate. The material and properties of the abrasive grains are not particularly limited, and for example, inorganic particles, organic particles, and organic-inorganic composite particles can all be used. Specific examples of inorganic particles include oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and red iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate; and the like. The alumina particles include α-alumina, intermediate aluminas other than α-alumina, and composites thereof. Intermediate alumina is a general term for alumina particles other than α-alumina, and specific examples include γ-alumina, δ-alumina, θ-alumina, η-alumina, κ-alumina, and composites thereof. Specific examples of organic particles include polymethylmethacrylate (PMMA) particles, poly(meth)acrylic acid particles, polyacrylonitrile particles, etc. Here, (meth)acrylic acid refers to acrylic acid and methacrylic acid in a comprehensive sense. The abrasive grains can be used alone or in combination of two or more kinds.
[0021] In some embodiments, the abrasive grains preferably include silica particles. The silica particles may be various silica particles mainly composed of silica. Here, the silica particles mainly composed of silica refer to particles in which 90% by weight or more, for example 95% by weight or more, or even 98% by weight or more of the particles are silica. Examples of silica particles that can be used include, but are not limited to, colloidal silica, fumed silica, precipitated silica, and the like. The silica particles may be heat-treated. The silica particles may be used alone or in combination of two or more kinds.
[0022] A suitable example of the silica particles is colloidal silica. As the colloidal silica, for example, it is preferable to use colloidal silica synthesized through particle growth in an aqueous phase, such as sodium silicate silica or alkoxide silica. With silica particles containing this type of colloidal silica, good surface accuracy can be suitably achieved. In addition, the effects of the technology disclosed herein (reduced polishing resistance and improved processability) can be effectively exhibited in an embodiment using colloidal silica as an abrasive. When the abrasive contains colloidal silica, the colloidal silica contained in the silica particles may be one type, or may be two or more types with different manufacturing conditions and / or physical properties. The colloidal silica may be surface-modified. Examples of surface modification include chemical modification such as introduction of functional groups and metal modification. In some preferred embodiments, the abrasive contained in the polishing composition contains colloidal silica alone. By using colloidal silica alone, better surface accuracy (for example, a surface with a reduced number of scratches) can be realized while maintaining processability.
[0023] Although not particularly limited, in an embodiment in which the abrasive grains include silica particles, silica particles having an average silanol group density of a predetermined value or less are preferably used. In some embodiments, the average silanol group density of the silica particles is, for example, 3.0 particles / nm from the viewpoint of improving processability. 2 It is appropriate to limit the number of particles to 2.5 / nm or less. 2In some preferred embodiments, the average silanol group density of the silica particles may be 2.0 / nm 2 Less than 1.8 particles / nm 2 or less, 1.6 particles / nm 2 or less. Silica particles with a high average silanol group density tend to have a low true density and low hardness. It is believed that silica particles with a low average silanol group density can improve processability based on their hardness. The technology disclosed herein is not limited to the above interpretation. In addition, the theoretical lower limit of the average silanol group density is 0 particles / nm 2 However, in practice, the lower limit of the average silanol group density is 0 / nm 2 From the viewpoint of reducing scratches, for example, 0.5 particles / nm 2 or more, and may be 1.0 particles / nm 2 More than 1.2 particles / nm is acceptable. 2 or more (e.g. 1.5 pieces / nm 2 or more).
[0024] The average silanol group density of the silica particles can be adjusted to an appropriate range below a predetermined value by selecting the method for producing the silica and by treatment such as heat treatment.
[0025] The average silanol group density of silica particles can be measured by Sears titration. Specifically, first, 1.50 g of silica particles as a solid content is collected in a 200 mL beaker, 100 mL of pure water is added to make a slurry, and then 30 g of sodium chloride is added to dissolve it. Next, 1 N hydrochloric acid is added to adjust the pH of the slurry to about 3.0 to 3.5, and pure water is added until the slurry becomes 150 mL. This slurry is adjusted to pH 4.0 with 0.1 N sodium hydroxide at 25 ° C. using an automatic titration device (manufactured by Hiranuma Sangyo Co., Ltd., COM-1700), and the volume V [L] of 0.1 N sodium hydroxide solution required to increase the pH from 4.0 to 9.0 by pH titration is measured. The average silanol group density is calculated by the following formula. Formula: ρ=(c×V×N A ×10-21 ) / (C×S) ρ: Average silanol group density [pieces / nm 2 ] c: Concentration of sodium hydroxide used in titration [mol / L] V: The volume of sodium hydroxide required to raise the pH from 4.0 to 9.0 [L] N A :Avogadro constant [pieces / mol] C: Mass of silica particles (solid content) [g] S: BET specific surface area of silica particles [nm 2 / g] The same applies to the embodiments described below.
[0026] The 50% cumulative diameter (D) in the particle size distribution based on the number of particles observed with a transmission electron microscope (TEM) of abrasive grains (e.g., silica grains) 50 ) is not particularly limited, and in some embodiments, from the viewpoint of processability, etc., it is preferably 5 nm or more, more preferably 10 nm or more. From the viewpoint of obtaining higher processability, the 50% cumulative diameter (D 50 ) is more preferably 15 nm or more, further preferably 20 nm or more, and may be 25 nm or more. In order to obtain a surface with higher surface accuracy, in some embodiments, the D 50 is suitably 200 nm or less, preferably 100 nm or less, more preferably 70 nm or less, further preferably 50 nm or less, particularly preferably 40 nm or less (eg, 30 nm or less).
[0027] The 50% cumulative diameter (D 50) can be obtained by the following method. First, an abrasive dispersion (e.g., silica dispersion) in which the abrasive grains to be measured (abrasive particles, e.g., silica particles) are dispersed in water is prepared. Then, a transmission electron microscope (TEM, Hitachi High-Technologies Corporation STEM HD-2700) is used to photograph a predetermined number (1000 or more) of particles that can be observed by TEM contained in the abrasive grains to be measured at a magnification (e.g., 200,000 to 400,000 times) at which about 100 particles can be observed in one field of view, and a TEM image is obtained. Then, the area of each particle is calculated from the obtained TEM image, and the diameter of an ideal circle (perfect circle) having the same area as the calculated area is calculated as the particle size of each particle. The particle size distribution based on the number of particles based on the TEM observation can be obtained by plotting the calculated particle diameters on the horizontal axis and the cumulative number (%) on the vertical axis for each particle constituting the abrasive grain. The 50% cumulative diameter (D 50 ) is the particle size corresponding to the point where the cumulative number is 50% in the particle size distribution. The particle size distribution can be determined using image analysis software MacView manufactured by Mountech Co., Ltd. The same applies to the examples described later. In addition, the above-mentioned predetermined number, i.e., the number of particles for which the particle diameter of each particle is calculated, is suitably 1000 or more, preferably 1500 or more, from the viewpoint of improving measurement accuracy and reproducibility. There is no particular upper limit to the above-mentioned predetermined number. From the viewpoint of measurement efficiency, the above-mentioned predetermined number may be, for example, 5000 or less, or may be 2500 or less.
[0028] The particle shape of the abrasive grains (e.g., silica grains) is not particularly limited, and may be, for example, spherical or non-spherical. When the polishing composition disclosed herein is used in the finish polishing process of Ni-P substrate, a shape close to spherical is preferred.
[0029] Although not particularly limited, the average aspect ratio of the abrasive grains (e.g., silica particles) is in principle 1.0 or more, and from the viewpoint of processability, it may be, for example, 1.03 or more, preferably 1.05 or more, more preferably 1.08 or more, even more preferably 1.10 or more (e.g., more than 1.10), may be 1.12 or more, or may be 1.15 or more. In addition, from the viewpoint of efficiently increasing the surface accuracy, in some embodiments, the average aspect ratio is suitably 1.30 or less. By reducing the average aspect ratio, the abrasive grains are easily rolled and moved, so that the polishing resistance is reduced, and processing is stabilized, and scratches can be more preferably reduced. From such a viewpoint, the average aspect ratio is preferably 1.25 or less, more preferably 1.22 or less, even more preferably 1.20 or less, and particularly preferably 1.18 or less. Here, the average aspect ratio of the abrasive grains refers to the average value of the major axis / minor axis ratio of each particle constituting the abrasive grains, that is, the number-average aspect ratio. Hereinafter, unless otherwise specified, the average aspect ratio in this specification means the above number-average aspect ratio.
[0030] The average aspect ratio of the abrasive grains is measured based on TEM observation. Specifically, when obtaining the number-based particle size distribution based on the TEM observation, the long side length (long axis value) of the smallest rectangle circumscribing each particle image from the acquired TEM image is divided by the short side length (short axis value) to calculate the long axis / short axis ratio (aspect ratio) of each particle. Then, the aspect ratios of the predetermined number of particles are arithmetically averaged to obtain the average aspect ratio (number-average aspect ratio). The aspect ratios can be obtained using image analysis software MacView manufactured by Mountech Co., Ltd. The same applies to the examples described later. In addition, the above-mentioned predetermined number, i.e., the number of particles for which the aspect ratio of each particle is calculated, is suitably 1000 or more, preferably 1500 or more, from the viewpoint of improving measurement accuracy and reproducibility. There is no particular upper limit to the above-mentioned predetermined number. From the viewpoint of measurement efficiency, the above-mentioned predetermined number may be, for example, 5000 or less, or may be 2500 or less.
[0031] The content of abrasive grains (e.g., silica particles) in the polishing composition is not particularly limited, and in some embodiments, it is, for example, 0.1% by weight or more, preferably 0.5% by weight or more, more preferably 1% by weight or more, and even more preferably 3% by weight or more. By increasing the content of abrasive grains, higher processability tends to be realized. From the viewpoint of the surface smoothness of the substrate after polishing and the dispersion stability of the abrasive grains, in some embodiments, the content is appropriately 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, and even more preferably 10% by weight or less, for example, 8% by weight or less, and may be 6% by weight or less, or 4% by weight or less. In addition, when multiple types of abrasive grains are contained, the content is the total content of them.
[0032] In some preferred embodiments, the polishing composition may substantially contain only silica particles (preferably colloidal silica) as abrasive grains. Here, substantially containing only silica particles (e.g., colloidal silica) means that the proportion of silica particles (e.g., colloidal silica) in the total solid content of the polishing composition is 99% by weight or more, more preferably 99.5% by weight or more, and even more preferably 99.9% by weight or more. In such an embodiment, the application effect of the technology disclosed herein can be preferably exhibited.
[0033] The polishing composition disclosed herein can be preferably implemented in an embodiment that does not substantially contain alumina particles. Examples of the alumina particles include α-alumina particles. Such a polishing composition prevents quality degradation caused by the use of alumina particles. Examples of quality degradation include the occurrence of scratches and dents, alumina residue, and puncture defects. In this specification, "substantially does not contain alumina particles" means that the proportion of the alumina particles in the total solid content contained in the polishing composition is 1% by weight or less, more preferably 0.5% by weight or less, for example 0.1% by weight or less. A polishing composition with a proportion of 0% by weight of alumina particles, that is, a polishing composition that does not contain alumina particles, is particularly preferred. In addition, the polishing composition disclosed herein can be preferably implemented in an embodiment that does not substantially contain α-alumina particles.
[0034] (acid) The polishing composition disclosed herein contains an acid. The acid functions to chemically polish the Ni-P substrate. The acid may be either an inorganic acid or an organic acid. The acid may be used alone or in combination of two or more.
[0035] Specific examples of inorganic acids include phosphoric acid (orthophosphoric acid), nitric acid, sulfuric acid, hydrochloric acid, boric acid, sulfamic acid, phosphinic acid, phosphonic acid, pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, hexametaphosphoric acid, carbonic acid, hydrofluoric acid, sulfurous acid, thiosulfuric acid, chloric acid, perchloric acid, chlorous acid, hydroiodic acid, periodic acid, iodic acid, hydrobromic acid, perbromic acid, bromic acid, chromic acid, and nitrous acid.
[0036] Examples of the organic acid include organic carboxylic acid, organic phosphonic acid, organic sulfonic acid, amino acid, etc. The number of carbon atoms contained in these organic acids is, for example, about 1 to 18, and preferably, for example, about 1 to 10. Specific examples of organic acids include malonic acid, citric acid, isocitric acid, 1,2,4-butanetricarboxylic acid, maleic acid, malic acid, glycolic acid, succinic acid, itaconic acid, iminodiacetic acid, gluconic acid, lactic acid, mandelic acid, tartaric acid, formic acid, acetic acid, propionic acid, butyric acid, adipic acid, oxalic acid, valeric acid, enanthic acid, caproic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, cyclohexanecarboxylic acid, phenylacetic acid, and benzoic acid. Organic carboxylic acids such as crotonic acid, oleic acid, linoleic acid, linolenic acid, ricinoleic acid, methacrylic acid, glutaric acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, tartronic acid, glyceric acid, hydroxybutyric acid, hydroxyacetic acid, hydroxybenzoic acid, salicylic acid, methylenesuccinic acid, gallic acid, ascorbic acid, nitroacetic acid, oxaloacetic acid, chloroacetic acid, dichloroacetic acid, trichloroacetic acid, pyridine carboxylic acids such as nicotinic acid and picolinic acid; methyl acid phosphate, ethyl ester ... Chill acid phosphate, ethyl glycol acid phosphate, isopropyl acid phosphate, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethanehydroxy-1,1,2-triphosphonic acid organic phosphonic acids such as ethanesulfonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, α-methylphosphonosuccinic acid, aminopoly(methylenephosphonic acid); organic sulfonic acids such as ethanesulfonic acid, aminoethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, 2-naphthalenesulfonic acid, sulfosuccinic acid, 10-camphorsulfonic acid, taurine;Amino acids such as glycine, alanine, glutamic acid, aspartic acid, valine, leucine, isoleucine, serine, threonine, cysteine, methionine, phenylalanine, tryptophan, tyrosine, proline, cystine, glutamine, asparagine, lysine, and arginine;
[0037] Examples of preferred acids from the viewpoint of processability include phosphoric acid, phosphonic acid, malonic acid, citric acid, maleic acid, hydrochloric acid, nitric acid, sulfuric acid, sulfamic acid, phytic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, etc. Among these, preferred acids include phosphoric acid, phosphonic acid, malonic acid, citric acid, and maleic acid.
[0038] The acid may be used in the form of a salt of the acid. Examples of the salt include metal salts, ammonium salts, alkanolamine salts, etc. of the above-mentioned inorganic acids and organic acids. Examples of the metal salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts. Examples of the ammonium salts include quaternary ammonium salts such as tetramethylammonium salts and tetraethylammonium salts. Examples of the alkanolamine salts include monoethanolamine salts, diethanolamine salts, and triethanolamine salts.
[0039] Specific examples of salts that can be contained in the polishing composition disclosed herein include alkali metal phosphates and alkali metal hydrogen phosphates such as tripotassium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, trisodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate; alkali metal salts of the organic acids exemplified above; and, in addition, alkali metal salts of glutamic acid diacetate, alkali metal salts of diethylenetriaminepentaacetate, alkali metal salts of hydroxyethylethylenediaminetriacetate, and alkali metal salts of triethylenetetraminehexaacetate. The alkali metal in these alkali metal salts can be, for example, lithium, sodium, potassium, etc.
[0040] In some embodiments, the salt may be an inorganic acid salt such as an alkali metal salt or an ammonium salt of an inorganic acid. For example, in addition to the above-mentioned alkali metal phosphates and alkali metal hydrogen phosphates, potassium chloride, sodium chloride, ammonium chloride, potassium nitrate, sodium nitrate, ammonium nitrate, etc. may be used.
[0041] The acid and its salt can be used alone or in combination of two or more (for example, two or three). In some embodiments, the acid can be used in combination with a salt of an acid different from the acid. For example, the acid can be an inorganic acid, and the salt of the acid can be an inorganic acid.
[0042] The concentration of the acid in the polishing composition (when a plurality of kinds of acids are contained, the total concentration of the acids) is not particularly limited. In some embodiments, the concentration of the acid is usually 0.1% by weight or more, preferably 0.5% by weight or more, more preferably 0.8% by weight or more, even more preferably 1% by weight or more, even more preferably 1.2% by weight or more, particularly preferably 1.5% by weight or more, and may be 1.8% by weight or more. By increasing the concentration of the acid, the processability tends to be improved. In addition, in some embodiments, the concentration of the acid in the polishing composition is usually 15% by weight or less, preferably 10% by weight or less, more preferably 5% by weight or less, and may be 3% by weight or less. By limiting the content of the acid, the surface precision of the polishing object (Ni-P substrate) is easily improved.
[0043] (Oxidizing agent) The polishing composition disclosed herein contains an oxidizing agent. By containing an oxidizing agent, a polishing composition having high processability can be obtained. Examples of oxidizing agents include peroxides, nitric acid or its salts, periodic acid or its salts, peroxoacid or its salts, permanganic acid or its salts, chromic acid or its salts, oxyacid or its salts, metal salts, sulfuric acids, etc., but are not limited thereto. The oxidizing agents can be used alone or in combination of two or more. Specific examples of the oxidizing agent include hydrogen peroxide, sodium peroxide, barium peroxide, nitric acid, iron nitrate, aluminum nitrate, ammonium nitrate, peroxomonosulfuric acid, ammonium peroxomonosulfate, metal peroxomonosulfate, peroxodisulfate, ammonium peroxodisulfate, metal peroxodisulfate, peroxolinic acid, peroxosulfuric acid, sodium peroxoborate, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, hypobromous acid, hypoiodous acid, chloric acid, bromic acid, iodic acid, periodic acid, perchloric acid, hypochlorous acid, sodium hypochlorite, calcium hypochlorite, potassium permanganate, metal chromate, metal dichromate, iron chloride, iron sulfate, iron citrate, ammonium iron sulfate, etc. Preferred examples of the oxidizing agent include hydrogen peroxide, iron nitrate, periodic acid, peroxomonosulfuric acid, peroxodisulfuric acid, and nitric acid. It preferably contains at least hydrogen peroxide, and more preferably consists of hydrogen peroxide.
[0044] The content of the oxidizing agent in the polishing composition is preferably 0.01% by weight or more based on the amount of active ingredient, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, even more preferably 0.3% by weight or more, and may be 0.5% by weight or more, in consideration of the rate of oxidation of the object to be polished and therefore the processability. Also, in view of improving the surface accuracy of the object to be polished, in some embodiments, the content of the oxidizing agent in the polishing composition is preferably 5% by weight or less based on the amount of active ingredient, more preferably 1% by weight or less.
[0045] (Water-soluble polymer (A)) The polishing composition disclosed herein contains a water-soluble polymer (A). In some embodiments, the water-soluble polymer (A) is characterized by being composed of one or more monomer units (a) having an SP value of 12.5 or more and one or more monomer units (b) having an SP value of less than 12.5. By using the water-soluble polymer (A), it is possible to achieve both a reduction in polishing resistance and an improvement in processability. The reason for this is considered to be as follows. That is, it is presumed that the water-soluble polymer (A) is adsorbed to each interface of the polishing field, for example, a polishing pad or a Ni-P substrate, promotes the diffusion of the abrasive component, and the surface modification proceeds in the direction of mitigating the polishing stress. Note that the above mechanism is the inventors' consideration based on experimental results, and the technology disclosed herein is not limited to the above mechanism.
[0046] The water-soluble polymer (A) disclosed herein is typically a polymer produced by polymerization of a monomer, and has a plurality of monomer units derived from the monomer. In the above polymer, the monomer unit is also called a repeating unit. The monomer unit of the water-soluble polymer (A) refers to a structural unit derived from a monomer used in the synthesis of the water-soluble polymer (A), and has a structure corresponding to the monomer after being incorporated into the polymer. The monomer unit (a) may be a single monomer unit having an SP value of 12.5 or more derived from a single monomer, or may be composed of multiple monomer units having an SP value of 12.5 or more derived from multiple monomers. Similarly, the monomer unit (b) may be a single monomer unit having an SP value of less than 12.5 derived from a single monomer, or may be composed of multiple monomer units having an SP value of less than 12.5 derived from multiple monomers.
[0047] In some embodiments, the water-soluble polymer (A) is characterized by having an SP value in the range of 11 to 17. By using a water-soluble polymer (A) consisting of a monomer unit (a) having an SP value of 12.5 or more and a monomer unit (b) having an SP value of less than 12.5, and having an SP value in the range of 11 to 17, it is possible to preferably achieve both reduced polishing resistance and improved processability. In some preferred embodiments, the SP value of the water-soluble polymer (A) is 11.5 or more, more preferably 12.0 or more, even more preferably 12.5 or more, and even more preferably 13.0 or more, from the viewpoint of solubility in water, etc. In some other embodiments, the SP value of the water-soluble polymer (A) may be 14.0 or more, 15.0 or more, or 16.0 or more. In some embodiments, the upper limit of the SP value of the water-soluble polymer (A), from the viewpoint of introducing a moderately hydrophobic monomer unit (b) into the water-soluble polymer (A), is preferably 16.0 or less, more preferably 15.0 or less, even more preferably 14.0 or less, even more preferably 13.5 or less, and may be 13.0 or less, 12.5 or less, or 12.0 or less.
[0048] In this specification, the SP value means the solubility parameter, and its unit is (cal / cm 3 ) 1 / 2 The SP value of the monomer unit can be calculated by the Fedors method based on the following formula:
number
[0049] The SP value of a water-soluble polymer (A) consisting of a plurality of monomer units is calculated based on the following formula: the molar volume fraction V' of each monomer unit in the water-soluble polymer (A) is calculated from the molar volume V of each monomer unit and the molar ratio α of each monomer unit, and the molar volume fraction V' is multiplied by the SP value δ of each monomer unit.
number
[0050] Although not particularly limited, the monomer used for synthesizing the water-soluble polymer (A) is preferably a vinyl monomer. Here, the vinyl monomer is a compound having a vinyl group having radical polymerizability. The water-soluble polymer (A) is preferably obtained by copolymerizing two or more kinds of vinyl monomers.
[0051] The water-soluble polymer (A) may contain one or more types of monomer units (a) having an SP value of 12.5 or more. As the monomer (a) forming the monomer unit (a), one or more suitable monomers having an SP value of 12.5 or more may be selected and used. Although not particularly limited, it is preferable to select one or more monomers having an SP value of 12.5 or more from, for example, a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, and an amide group-containing monomer (e.g., (meth)acrylamide) and use them. Note that (meth)acryl refers to acrylic and methacrylic in a comprehensive sense, and similarly, (meth)acrylate, which will be described later, also includes acrylate and methacrylate, and (meth)acryloyl is also used to mean acryloyl and methacryloyl.
[0052] The water-soluble polymer (A) may contain one or more types of monomer units (b) having an SP value of less than 12.5. The monomer (b) forming the monomer unit (b) may be selected from various monomers having an SP value of less than 12.5. Although not particularly limited, the monomer (b) is preferably selected from, for example, amide group-containing monomers (e.g., N,N-dialkyl(meth)acrylamide, N-monoalkyl(meth)acrylamide) and aromatic vinyl monomers (styrene, vinylnaphthalene, etc.) having an SP value of less than 12.5.
[0053] Suitable examples of the monomer units (a) and (b) include those shown in Table 1 below.
[0054] [Table 1]
[0055] The abbreviations for the monomers in Table 1 are as follows. AA: Acrylic acid MA: methacrylic acid ATBS: 2-acrylamido-2-methylpropanesulfonic acid AM: Acrylamide TBAA: N-tert-butylacrylamide DMAM: N,N-Dimethylacrylamide DEAM: N,N-diethylacrylamide DPAM: N,N-dipropylacrylamide DIPAM: N,N-diisopropylacrylamide DBAM: N,N-dibutylacrylamide St: styrene
[0056] In some embodiments, the SP value of the monomer unit (a) constituting the water-soluble polymer (A) is preferably 13.0 or more, more preferably 13.5 or more, and even more preferably 14.0 or more, from the viewpoint of introducing a portion having a predetermined or higher hydrophilicity into the water-soluble polymer (A). In some other embodiments, the SP value of the monomer unit (a) may be 15.0 or more, 17.0 or more, or 19.0 or more. In some embodiments, from the viewpoint of copolymerizability with the monomer unit (b), the SP value of the monomer unit (a) may be 20 or less, 19.0 or less, 18.0 or less, 17.0 or less, 16.0 or less, 15.0 or less, 14.0 or less, or 13.0 or less.
[0057] In some embodiments, the SP value of the monomer unit (b) constituting the water-soluble polymer (A) is preferably 12.0 or less, more preferably 11.5 or less, and may be 11.0 or less or 10.5 or less, from the viewpoint of introducing a portion having a predetermined or higher hydrophobicity into the water-soluble polymer (A). In some embodiments, the SP value of the monomer unit (b) may be 8.0 or more, 9.0 or more, 9.5 or more, 10.0 or more, 10.5 or more, 11.0 or more, 11.5 or more, or 12.0 or more, from the viewpoint of the solubility in water of the water-soluble polymer (A) and copolymerizability with the monomer unit (a).
[0058] Although not particularly limited, in some embodiments, the difference (ab) between the SP value (a) of the monomer unit (a) and the SP value (b) of the monomer unit (b) is preferably 1.0 or more, more preferably 1.5 or more, even more preferably 2.0 or more, and particularly preferably 2.5 or more, from the viewpoint of effectively exerting the effect of having the hydrophilic monomer unit (a) and the hydrophobic monomer unit (b). In some embodiments, the difference (ab) is suitably 10 or less, preferably 7 or less, more preferably 5 or less, even more preferably 4 or less, and particularly preferably 3 or less, from the viewpoint of copolymerizability, etc.
[0059] The molar number of the monomer unit (a) in the total number of moles of the monomer units constituting the water-soluble polymer (A) (the molar ratio of the monomer unit (a)) is not particularly limited, but in some embodiments, from the viewpoint of the solubility of the water-soluble polymer (A) in water, it may be 30 mol% or more, or 40 mol% or more. In some preferred embodiments, the molar ratio of the monomer unit (a) is 50 mol% or more (e.g., more than 50 mol%), more preferably 60 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, particularly preferably 80 mol% or more, and may be 85 mol% or more. In some embodiments, from the viewpoint of obtaining the effect of introducing the monomer unit (b), the molar ratio of the monomer unit (a) is usually, for example, 99 mol% or less, suitably 97 mol% or less, preferably 95 mol% or less, more preferably 90 mol% or less, and may be 85 mol% or less. In some other embodiments, the molar ratio of the monomer unit (a) may be 80 mol% or less, 70 mol% or less, 60 mol% or less, 50 mol% or less, or 40 mol% or less.
[0060] The molar number of the monomer unit (b) in the total molar number of the monomer units constituting the water-soluble polymer (A) (the molar ratio of the monomer unit (b)) is not particularly limited, but in some embodiments, from the viewpoint of effectively exerting the effect of introducing the hydrophobic monomer unit (b), it may be 1 mol% or more, or 3 mol% or more. In some preferred embodiments, the molar ratio of the monomer unit (b) is 5 mol% or more, more preferably 10 mol% or more, and even more preferably 15 mol% or more. In some other embodiments, the molar ratio of the monomer unit (b) may be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, or 60 mol% or more. In some embodiments, from the viewpoint of the solubility of the water-soluble polymer (A) in water, the molar ratio of the monomer unit (b) is preferably 70 mol% or less, more preferably 60 mol% or less, even more preferably 50 mol% or less, still more preferably 40 mol% or less, even more preferably 30 mol% or less, particularly preferably 20 mol% or less, or may be 15 mol% or less, 10 mol% or less, or 5 mol% or less.
[0061] The water-soluble polymer (A) disclosed in the present specification includes embodiments without restrictions on the above-mentioned characteristics regarding the SP value (comprising monomer units (a) having an SP value of 12.5 or more and monomer units (b) having an SP value of less than 12.5, and having an SP value within the range of 11 to 17), and in such embodiments, the water-soluble polymer (A) is not limited to those that satisfy the above-mentioned characteristics regarding the SP value.
[0062] In some embodiments, it is preferable to use a copolymer of vinyl monomers containing at least one monomer selected from the following structures I and II as the water-soluble polymer (A). By using a water-soluble polymer (A) having such a chemical structure, it is possible to preferably achieve both reduced polishing resistance and improved processability. [ka] (In Structure I, R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a linear or branched alkyl or alkenyl group having 10 or less carbon atoms, or R2 and R3 are bonded to each other to form a cyclic structure.)
[0063] Although not intended to be particularly limited, the water-soluble polymer (A) having the above chemical structure, i.e., the water-soluble polymer (A) being a copolymer containing a hydrophobic monomer having structure I or II, is believed to adsorb to the polishing pad surface and the nickel metal surface of the Ni-P substrate, thereby reducing the resistance during polishing and improving the processability. As a result, it is believed that the reduction of polishing resistance and the improvement of processability are simultaneously realized. The monomers selected from the above structures I and II can be used alone or in combination of two or more.
[0064] In some embodiments, the vinyl monomer used in the synthesis of the water-soluble polymer (A) is a monomer having the above structure I. The monomer having the above structure I can be used alone or in combination of two or more. Although not particularly limited, R1 in the above structure I is preferably a hydrogen atom.
[0065] In the above structure I, in the monomer in which R2 and R3 are an alkyl group or an alkenyl group, the carbon number of R2 and R3 is 1 or more, preferably 2 or more, and may be 3 or more or 4 or more. The carbon number is preferably 8 or less, more preferably 6 or less, even more preferably 4 or less, and particularly preferably 3 or 2 or less. In addition, R2 and R3 are preferably linear alkyl groups. An example of the above structure I includes N,N-dialkyl(meth)acrylamide having two alkyl groups having 4 to 10 carbon atoms. Specific examples include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. The above N,N-dialkyl(meth)acrylamides can be used alone or in combination of two or more.
[0066] In the above structure I, in a monomer having a structure in which R2 and R3 are bonded to each other to form a cyclic structure, R2 and R3 are represented by -X-. X is an organic chain, for example, a carbon chain. X contains carbon atoms in the main chain, and may contain an oxygen atom (O) or a nitrogen atom (N) in the main chain or a side chain, or may contain a double bond. The number of carbon atoms in X is, for example, 4 to 10. X can be, for example, (CH2) n (wherein n is an integer of 4 to 10).
[0067] In some other embodiments, the vinyl monomer used in the synthesis of the water-soluble polymer (A) is a monomer having structure II, i.e., styrene. Alternatively, a styrene derivative such as styrene sulfonic acid can be used as the vinyl monomer instead of or in addition to the monomer having structure II.
[0068] In some embodiments, as the monomer having the above structure I or II, a monomer capable of forming a monomer unit (b) having the above SP value of less than 12.5 in the water-soluble polymer (A) is preferably used.
[0069] The molar number of the monomer selected from the structures I and II in the molar number of all monomer components forming the water-soluble polymer (A) is not particularly limited, but in some embodiments, from the viewpoint of effectively exerting the effect of copolymerizing the hydrophobic monomer selected from the structures I and II, it may be 1 mol% or more, or 3 mol% or more. In some preferred embodiments, the molar number of the monomer selected from the structures I and II is 5 mol% or more, more preferably 10 mol% or more, and even more preferably 15 mol% or more. In some other embodiments, the molar number of the monomer selected from the structures I and II may be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, or 60 mol% or more. In some embodiments, from the viewpoint of the solubility of the water-soluble polymer (A) in water, the number of moles of the monomer selected from the above structures I and II is preferably 70 mol % or less, more preferably 60 mol % or less, even more preferably 50 mol % or less, still more preferably 40 mol % or less, even more preferably 30 mol % or less, particularly preferably 20 mol % or less, or may be 15 mol % or less, 10 mol % or less, or 5 mol % or less.
[0070] In some embodiments, at least one of the vinyl monomers used in the synthesis of the water-soluble polymer (A) is preferably a carboxylic acid group-containing monomer. As the carboxylic acid group-containing monomer, a monomer having a carboxylic acid group and a vinyl group can be used without any particular limitation. Suitable examples of the carboxylic acid group-containing monomer include acrylic acid (AA) and methacrylic acid (MA). Other examples of the carboxylic acid group-containing monomer include carboxyalkyl (meth)acrylate, maleic acid, itaconic acid, vinyl benzoate, and the like. The carboxylic acid in the carboxylic acid group-containing monomer may be in the form of a salt such as a sodium salt or a potassium salt, or may be in the form of an acid anhydride. As the carboxylic acid group-containing monomer, a carboxylic acid group-containing monomer capable of forming the monomer unit (a) having an SP value of 12.5 or more in the water-soluble polymer (A) is preferably used. The carboxylic acid group-containing monomer can be used alone or in combination of two or more.
[0071] The molar number of the carboxylic acid group-containing monomer in the molar number of all monomer components forming the water-soluble polymer (A) is not particularly limited, but in some embodiments, from the viewpoint of the solubility of the water-soluble polymer (A) in water, it may be 30 mol% or more, or 40 mol% or more. In some preferred embodiments, the molar number of the carboxylic acid group-containing monomer is 50 mol% or more (e.g., more than 50 mol%), more preferably 60 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, particularly preferably 80 mol% or more, and may be 85 mol% or more. In some embodiments, from the viewpoint of obtaining the effect of copolymerizing the monomer selected from structures I and II, the molar number of the carboxylic acid group-containing monomer is usually, for example, 99 mol% or less, appropriately 97 mol% or less, preferably 95 mol% or less, more preferably 90 mol% or less, and even more preferably 85 mol% or less. In some other embodiments, the number of moles of the carboxylic acid group-containing monomer may be 80 mol % or less, 70 mol % or less, 60 mol % or less, 50 mol % or less, or 40 mol % or less.
[0072] In some preferred embodiments, it is preferable to use a copolymer of a carboxylic acid group-containing monomer and a monomer selected from structures I and II as the water-soluble polymer (A). In such embodiments, the water-soluble polymer (A) may be copolymerized with a monomer other than the carboxylic acid group-containing monomer and the monomer selected from structures I and II (hereinafter also referred to as "optional monomer"), or may not be substantially copolymerized, within a range that does not significantly impair the function of the copolymer and the effects of the invention. Such optional monomers are typically vinyl monomers, such as sulfonic acid group-containing monomers, (meth)acrylamide, N-monoalkyl (meth)acrylamide, etc. The copolymerization ratio of the carboxylic acid group-containing monomer and the optional monomer other than the monomer selected from structures I and II in the water-soluble polymer (A) is, for example, less than 30 mol%, may be less than 20 mol%, may be less than 10 mol%, may be less than 5 mol%, may be less than 3 mol%, may be less than 1 mol%.
[0073] Although not particularly limited, the weight average molecular weight (Mw) of the water-soluble polymer (A) is usually, for example, about 2,000 or more, and may be 4,000 or more. In some preferred embodiments, the Mw is 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, and particularly preferably 12,000 or more. A water-soluble polymer (A) with a large Mw tends to easily improve processability. In some embodiments, the Mw of the water-soluble polymer (A) may be 100,000 or less (for example, less than 100,000), or 70,000 or less. In some preferred embodiments, the Mw is 50,000 or less, 30,000 or less, 20,000 or less, or 15,000 or less. By using a water-soluble polymer (A) having an appropriate Mw within the above range, it is possible to preferably achieve both reduced polishing resistance and improved processability.
[0074] The Mw of the water-soluble polymer (A) can be a value based on aqueous gel permeation chromatography (GPC). The measurement can be carried out, for example, under the following conditions. [GPC measurement conditions] Equipment: Tosoh HLC-8320GPC Column: Tosoh Corporation, TSKgel GMPWxL Eluent: 0.1N sodium nitrate Flow rate: 0.5mL / min Temperature: 40℃ Detection: Differential refractive index detector Sample: 0.1% by weight (injection volume 100 μL) Standard samples: PEG and PEO with known molecular weights
[0075] The method for obtaining the water-soluble polymer (A) is not particularly limited, and various polymerization methods known as a method for synthesizing water-soluble polymers can be appropriately adopted. For example, an aqueous solution polymerization method can be preferably adopted. As the solvent (polymerization solvent) used in the aqueous solution polymerization, an aqueous solvent (typically water) is used, and in addition to water, an appropriate amount of alcohols such as isopropyl alcohol and ketones such as acetone can be contained. The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators depending on the type of polymerization method. For example, a radical polymerization initiator such as an azo-based polymerization initiator or a peroxide-based polymerization initiator can be preferably used. As the polymerization initiator, a water-soluble redox-based polymerization initiator may be used. The amount of the polymerization initiator used can be a normal amount depending on the polymerization method, polymerization mode, etc., and is not particularly limited. For example, the amount of the polymerization initiator can be within the range of about 0.001 to 15 parts by weight (preferably about 0.01 to 10 parts by weight, for example about 0.1 to 10 parts by weight) relative to 100 parts by weight of the total monomer components to be polymerized. During the polymerization, an appropriate amount of a chain transfer agent may be added for the purpose of adjusting the molecular weight, etc. The polymerization temperature can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, etc., and can be, for example, about 60° C. to 100° C. The polymerization time is preferably within a range of about 2 to 20 hours (for example, 3 to 10 hours). After the polymerization reaction, neutralization with a basic compound may be performed as necessary.
[0076] The concentration of the water-soluble polymer (A) in the polishing composition is not particularly limited. In some embodiments, the concentration is, for example, 0.0001% by weight or more, and may be 0.0005% by weight or more. From the viewpoint of effectively exerting the effect of containing the water-soluble polymer (A), in some preferred embodiments, the concentration is 0.001% by weight or more, may be 0.005% by weight or more, may be 0.01% by weight or more, or may be 0.03% by weight or more. In some embodiments, the concentration of the water-soluble polymer (A) is suitably 3% by weight or less, and may be 2% by weight or less. From the viewpoint of processability and cleaning removability after polishing, in some preferred embodiments, the concentration of the water-soluble polymer (A) is 1% by weight or less (for example, less than 1% by weight), more preferably 0.2% by weight or less, even more preferably 0.1% by weight or less (for example, less than 0.1% by weight), may be 0.07% by weight or less, or may be 0.05% by weight or less.
[0077] The amount of water-soluble polymer (A) contained in the polishing composition can also be specified by the relative relationship with the abrasive grains contained in the polishing composition. In some embodiments, the content of the water-soluble polymer (A) relative to 100 parts by weight of the abrasive grains contained in the polishing composition is, for example, appropriate to be 0.001 parts by weight or more, preferably 0.01 parts by weight or more, more preferably 0.1 parts by weight or more, even more preferably 0.5 parts by weight or more, and may be 1 part by weight or more. In some embodiments, the content of the water-soluble polymer (A) relative to 100 parts by weight of the abrasive grains is appropriate to be about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, even more preferably 2 parts by weight or less, and may be 1.5 parts by weight or less. By using an appropriate amount of water-soluble polymer (A) relative to the amount of abrasive grains, it is possible to preferably achieve both reduced polishing resistance and improved processability.
[0078] (water) The polishing composition disclosed herein contains water. As the water, ion-exchanged water, pure water, ultrapure water, distilled water, etc. can be preferably used. The ion-exchanged water may be deionized water.
[0079] (Sulfonic acid (salt) group-containing polymer) In some preferred embodiments, the polishing composition contains a polymer having a sulfonic acid (salt) group (hereinafter also referred to as "sulfonic acid (salt) group-containing polymer"). The above-mentioned sulfonic acid (salt) group-containing polymer does not include those corresponding to the water-soluble polymer (A). By using a sulfonic acid (salt) group-containing polymer in addition to the water-soluble polymer (A), it is possible to better reduce the polishing resistance while maintaining high processability. Here, the sulfonic acid (salt) group-containing polymer refers to a polymer containing at least one type of repeating unit X having a sulfonic acid (salt) group as a repeating unit constituting the polymer. The term "sulfonic acid (salt)" is a concept that includes sulfonic acid and sulfonic acid salts, and refers to at least one of sulfonic acid and sulfonic acid salts. Since the sulfonic acid (salt) group is anionic, the sulfonic acid (salt) group-containing polymer also has anionic properties. The sulfonic acid (salt) group-containing polymer can be used alone or in combination of two or more.
[0080] The repeating unit X of the sulfonic acid (salt) group-containing polymer may be a repeating unit derived from a monomer having at least one sulfonic acid (salt) group in one molecule. Examples of monomers having a sulfonic acid (salt) group include styrenesulfonic acid, isoprene sulfonic acid, vinylsulfonic acid, allylsulfonic acid, isoamylenesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, and methallylsulfonic acid. The sulfonic acid (salt) group-containing polymer may contain two or more types of the repeating unit X. The sulfonic acid (salt) group-containing polymer may further contain a repeating unit that does not have a sulfonic acid (salt) group. The repeating unit that does not have a sulfonic acid (salt) group may be a repeating unit that has an anionic functional group other than sulfonic acid (salt), or may be a repeating unit that does not have an anionic functional group.
[0081] An example of a repeating unit having an anionic functional group other than sulfonic acid (salt) is a repeating unit Y having a carboxy group. The repeating unit Y may be, for example, a repeating unit derived from (meth)acrylic acid. Here, "(meth)acrylic acid" is a concept that includes one or both of acrylic acid and methacrylic acid. The sulfonic acid (salt) group-containing polymer may be a (meth)acrylic acid / sulfonic acid copolymer containing a carboxy group-containing repeating unit Y and a repeating unit X derived from (meth)acrylic acid. Examples of the (meth)acrylic acid / sulfonic acid copolymer include a (meth)acrylic acid / isoprene sulfonic acid copolymer, a (meth)acrylic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer, and a (meth)acrylic acid / isoprene sulfonic acid / 2-acrylamido-2-methylpropane sulfonic acid copolymer. The (meth)acrylic acid / sulfonic acid copolymer may further contain a repeating unit that does not have a sulfonic acid (salt) group and is not derived from a (meth)acrylic acid monomer.
[0082] In some embodiments, the sulfonic acid (salt) group-containing polymer may be a sulfonic acid (salt) group-containing polymer that does not contain a repeating unit Y having a carboxy group. The sulfonic acid (salt) group-containing polymer that does not contain a repeating unit Y may further contain a repeating unit that does not have a sulfonic acid (salt) group and a carboxy group (e.g., a repeating unit that does not have an anionic functional group).
[0083] An example of the sulfonic acid (salt) group-containing polymer is a polymer in which the molar ratio of sulfonic acid (salt) group-containing repeating unit X to the total molar ratio of repeating units contained in the molecular structure of the polymer is 95% or more. For example, a sulfonic acid (salt) group-containing polymer substantially consisting of repeating unit X can be used. In such a sulfonic acid (salt) group-containing polymer, the molar ratio of the repeating unit X may be, for example, 98% or more, 99.5% or more, or 99.9% or more. In some embodiments, the sulfonic acid (salt) group-containing polymer may be a sulfonic acid (salt) group-containing polymer in which the molar ratio of the repeating unit X is 100%, that is, a sulfonic acid (salt) group-containing polymer consisting only of repeating unit X having a sulfonic acid (salt) group. Examples of such a sulfonic acid (salt) group-containing polymer include a homopolymer consisting of any one of the above sulfonic acid (salt) group-containing monomers, and a copolymer consisting of two or more sulfonic acid (salt) group-containing monomers. Examples of the homopolymer include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyisoamylene sulfonic acid, etc. Among these, polystyrene sulfonic acid, that is, a homopolymer of styrene sulfonic acid, is preferred.
[0084] In some preferred embodiments, the sulfonic acid (salt) group-containing polymer is a polymer having a main chain and a sulfonic acid (salt) group, and a chemical structure having an aromatic ring in the main chain. The main chain of the sulfonic acid (salt) group-containing polymer is typically composed of a plurality of repeating units, and the main chain contains an aromatic ring. Examples of structures having an aromatic ring in the main chain include structures such as benzene, naphthalene, and anthracene, as well as melamine and lignin structures, which may exist in the main chain with an alkyl group such as a methyl group intervening therebetween. The sulfonic acid (salt) group is bonded to the main chain as a side chain, and is usually bonded directly to the main chain, but is not limited thereto, and may be linked to the main chain via another group.
[0085] Suitable examples of the sulfonic acid (salt) group-containing polymer having the above chemical structure include polyalkylarylsulfonic acid compounds such as naphthalenesulfonic acid formaldehyde condensates or salts thereof, methylnaphthalenesulfonic acid formaldehyde condensates or salts thereof, anthracenesulfonic acid formaldehyde condensates or salts thereof; melamine formalin resin sulfonic acid compounds such as melaminesulfonic acid formaldehyde condensates or salts thereof; ligninsulfonic acid compounds such as ligninsulfonic acid or salts thereof, modified ligninsulfonic acid or salts thereof; and aromatic aminosulfonic acid compounds such as aminoarylsulfonic acid-phenol-formaldehyde condensates or salts thereof.
[0086] When the sulfonic acid (salt) group-containing polymer is in the form of a neutralized salt, the sulfonic acid (salt) group-containing polymer may be in the form of an alkali metal salt such as Na or K, an alkaline earth metal salt such as Ca, an ammonium salt, an alkylammonium salt, an alkanolamine salt such as monoethanolamine, etc. The sulfonic acid (salt) group-containing polymer may be preferably used in the form of an alkali metal salt such as a Na salt, for example.
[0087] The Mw of the sulfonic acid (salt) group-containing polymer is not particularly limited, and may be, for example, about 400 or more, or 1000 or more. In some preferred embodiments, the Mw of the sulfonic acid (salt) group-containing polymer is, for example, 1500 or more, may be 2000 or more, or may be 2500 or more. The upper limit of the Mw of the sulfonic acid (salt) group-containing polymer is, for example, 300,000 or less, or may be 100,000 or less. In some preferred embodiments, the Mw of the sulfonic acid (salt) group-containing polymer is, for example, 50,000 or less, may be 10,000 or less (for example, less than 10,000), may be 9,000 or less, or may be 5,000 or less. The weight average molecular weight determined by GPC can be used as the Mw of the sulfonic acid (salt) group-containing polymer. The measurement conditions of GPC can be the same as the measurement conditions of the Mw of the water-soluble polymer (A) described above.
[0088] In an embodiment in which the polishing composition contains a sulfonic acid (salt) group-containing polymer, the concentration of the sulfonic acid (salt) group-containing polymer in the polishing composition is not particularly limited, and may be, for example, 0.0001% by weight or more, or 0.0005% by weight or more. In some preferred embodiments, the concentration of the sulfonic acid (salt) group-containing polymer is, for example, 0.001% by weight or more, or 0.005% by weight or more, or 0.01% by weight or more, from the viewpoint of effectively exerting the effect of adding the sulfonic acid (salt) group-containing polymer. In addition, in some embodiments, from the viewpoint of processability and cleaning removability after polishing, the concentration of the sulfonic acid (salt) group-containing polymer is usually appropriate to be less than 1% by weight, preferably 0.2% by weight or less, more preferably 0.1% by weight or less, or 0.07% by weight or less, 0.05% by weight or less, or 0.03% by weight or less.
[0089] In an embodiment in which the polishing composition contains a sulfonic acid (salt) group-containing polymer, the ratio of the water-soluble polymer (A) to the sulfonic acid (salt) group-containing polymer is appropriately set so that the effects of the technology disclosed herein are preferably exhibited, and is not limited to a specific range. A Concentration of sulfonic acid (salt) group-containing polymer C B Weight ratio (C B / C A ) is, for example, 0.01 or more, preferably 0.1 or more, may be 0.3 or more, or may be 0.5 or more. In some embodiments, the weight ratio (C B / C A ) is, for example, 30 or less, preferably 10 or less, more preferably 5 or less, even more preferably 3 or less, and may be 1 or less (for example, less than 1). By setting the ratio of the water-soluble polymer (A) to the sulfonic acid (salt) group-containing polymer in an appropriate range, a more excellent effect of reducing polishing resistance can be obtained.
[0090] (Optional water-soluble polymer) The polishing composition disclosed herein may contain a water-soluble polymer (hereinafter also referred to as "any water-soluble polymer") as an optional component. The optional water-soluble polymer does not include those that fall under the category of water-soluble polymer (A) and does not include those that fall under the category of sulfonic acid (salt) group-containing polymers. The optional water-soluble polymer may, for example, protect the substrate during polishing and suppress the occurrence of defects (e.g., scratches) on the substrate surface. The optional water-soluble polymer may be a homopolymer or a copolymer, and any of anionic polymers, nonionic polymers, cationic polymers, and amphoteric polymers can be used. Examples of such optional water-soluble polymers include polyacrylic acid and its salts, polyvinyl acetate, polymaleic acid, polyitaconic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyglycerin, polyvinylpyrrolidone, copolymers of polyvinylpyrrolidone and polyacrylic acid and / or vinyl acetate, diallylamine hydrochloride sulfur dioxide copolymers, carboxymethylcellulose and its salts, hydroxyethyl cellulose, hydroxypropyl cellulose, pullulan, chitosan and its salts, and the like, but are not limited thereto. The optional water-soluble polymers may be used alone or in combination of two or more.
[0091] The Mw of the water-soluble polymer may be, for example, 2000 or more, or 2500 or more. In some embodiments, the Mw of the water-soluble polymer is preferably 3000 or more, more preferably 5000 or more, and may be 7000 or more, or 9000 or more. The upper limit of the Mw of the water-soluble polymer is not particularly limited, and may be, for example, 1.5 million or less, 1 million or less, 500,000 or less, 300,000 or less, 200,000 or less, 100,000 or less, 70,000 or less, 50,000 or less, or 30,000 or less. The weight average molecular weight obtained by GPC can be adopted as the Mw of the water-soluble polymer. The measurement conditions of GPC can be the same as the measurement conditions of Mw of the water-soluble polymer (A).
[0092] In the embodiment in which any water-soluble polymer is used, the content of the water-soluble polymer in the polishing composition can be appropriately set within a range in which the effect of the present invention is not significantly hindered. In addition, the polishing composition disclosed herein can be implemented in an embodiment in which any water-soluble polymer is not substantially contained. From this viewpoint, in the embodiment in which the polishing composition contains any water-soluble polymer and the embodiment in which the polishing composition does not substantially contain any water-soluble polymer, the proportion of the water-soluble polymer in the total water-soluble polymer (including the water-soluble polymer (A) and the sulfonic acid (salt) group-containing polymer) contained in the polishing composition may be 80% by weight or less, 50% by weight or less (for example, less than 50% by weight), 30% by weight or less, 20% by weight or less, 10% by weight or less, or 5% by weight or less (for example, 0 to 5% by weight).
[0093] (Basic compounds) The polishing composition may contain a basic compound as necessary for the purpose of pH adjustment, etc. Here, the basic compound refers to a compound that has the function of increasing the pH of the polishing composition by being added to the composition. Examples of basic compounds include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, quaternary ammonium compounds such as quaternary ammonium hydroxide, ammonia, amines, etc. The basic compounds may be used alone or in combination of two or more.
[0094] (chelating agent) The polishing composition disclosed herein may contain a chelating agent as necessary. By including a chelating agent, the occurrence of defects on the polished surface after polishing can be suppressed. Examples of the chelating agent include aminocarboxylic acid-based chelating agents and organic phosphonic acid-based chelating agents. Examples of the aminocarboxylic acid-based chelating agent include ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetate, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, glutamic acid diacetic acid, sodium glutamic acid diacetate, hydroxyethylethylenediaminetriacetic acid, sodium hydroxyethylethylenediaminetriacetate, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, triethylenetetraminehexaacetic acid, and sodium triethylenetetraminehexaacetate. Examples of organic phosphonic acid chelating agents include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, and α-methylphosphonosuccinic acid. Among them, preferred are glutamic acid diacetate, 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetrakis(methylenephosphonic acid) and diethylenetriaminepenta(methylenephosphonic acid). Particularly preferred chelating agents are glutamic acid diacetate and 1-hydroxyethylidene-1,1-diphosphonic acid. The chelating agents can be used alone or in combination of two or more.
[0095] The content of the chelating agent in the polishing composition is not particularly limited. The content of the chelating agent is usually 0.005% by weight or more, and may be 0.01% by weight or more, 0.1% by weight or more, or 0.5% by weight or more. The content of the chelating agent is usually 5% by weight or less, and may be 3% by weight or less, 2% by weight or less, or 1% by weight or less.
[0096] (Other Ingredients) The polishing composition disclosed herein may further contain known additives such as surfactants, preservatives, and antifungal agents that can be used in polishing compositions (for example, polishing compositions for magnetic disk substrates such as Ni-P substrates) as necessary, within the scope that does not significantly impair the effects of the present invention. For example, examples of preservatives and antifungal agents include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, phenoxyethanol, etc., but are not limited thereto.
[0097] (pH) The pH of the polishing composition disclosed herein is not particularly limited, and may be selected, for example, from the range of 0.5 to 6.5. From the viewpoint of processability, etc., in some preferred embodiments, the pH of the polishing composition is, for example, 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, and may be 2.5 or less, 2.0 or less, 1.8 or less, or 1.6 or less. In some embodiments, the pH of the polishing composition can be, for example, 1.0 or more, and it is appropriate to make it higher than 1.0, and from the viewpoint of suppressing roughness of the substrate surface after polishing, it is preferably 1.2 or more, more preferably 1.5 or more (for example, more than 1.5). The technology disclosed herein can be preferably implemented in an embodiment in which the pH of the polishing composition is 1.0 or more and 4.0 or less. The above-mentioned pH can be particularly preferably applied to a polishing composition for finish polishing of Ni-P substrates.
[0098] In the technique disclosed herein, the pH of the polishing composition can be determined by performing three-point calibration using a pH meter, then inserting a glass electrode into the composition to be measured. The standard solutions are, for example, oxalate pH standard solution: pH 1.68 (25°C), phthalate pH standard solution: pH 4.01 (25°C), neutral phosphate pH standard solution: pH 6.86 (25°C), and carbonate pH standard solution: pH 10.01 (25°C).
[0099] <Concentrate> The polishing composition disclosed herein may be in a concentrated form (i.e., in the form of a concentrated polishing liquid) before being supplied to an object to be polished (e.g., a magnetic disk substrate). Such a concentrated polishing composition (concentrate) is advantageous from the viewpoints of convenience and cost reduction during production, distribution, storage, etc. The concentration ratio can be, for example, about 1.5 to 20 times in terms of volume. From the viewpoint of storage stability of the concentrate, for example, a concentration ratio of about 2 to 10 times is appropriate. Such a concentrated liquid can be used in a form in which a polishing composition (polishing liquid) is prepared by diluting it at a desired timing, and the polishing liquid is supplied to an object to be polished. The dilution can be performed, for example, by adding water to the concentrated liquid and mixing it.
[0100] <Multi-component polishing composition> The polishing composition disclosed herein may be a one-component type or a multi-component type, including a two-component type. For example, the polishing composition may be configured so that a part A containing some of the components (e.g., components other than water) of the polishing composition and a part B containing the remaining components are mixed and used for polishing an object to be polished. Some preferred embodiments of the multi-component polishing composition are configured to contain a part A containing abrasive grains (e.g., a dispersion liquid further containing a dispersion medium for the abrasive grains) and a part B containing at least a part of the components other than the abrasive grains (e.g., an acid, a water-soluble polymer (A), etc.). These are stored separately, for example, before use, and can be mixed at the time of use to prepare a one-component polishing composition. When mixed, an oxidizing agent such as hydrogen peroxide, water for dilution, etc. can be further mixed.
[0101] <Polishing process> The polishing composition disclosed herein can be suitably used for polishing an object to be polished (here, a Ni-P substrate) in an embodiment including the following operations, for example. A preferred embodiment of the method for polishing an object to be polished using the polishing composition disclosed herein will be described below. That is, a polishing liquid (working slurry) containing any of the polishing compositions disclosed herein is prepared. The preparation of the polishing liquid may include adjusting the concentration (e.g., diluting) or adjusting the pH of the polishing composition to prepare the polishing liquid. Alternatively, the polishing composition may be used as it is as the polishing liquid.
[0102] Next, the polishing liquid is supplied to the object to be polished, and the object is polished. For example, the object to be polished is set in a general polishing device, and the polishing liquid is supplied to the surface of the object to be polished (the surface to be polished) through the polishing pad of the polishing device. For example, while continuously supplying the polishing liquid, the polishing pad is pressed against the surface of the object to be polished, and the two are moved relatively (for example, rotated).
[0103] The polishing pad that can be used is not particularly limited. For example, polishing pads such as hard foam polyurethane type, nonwoven fabric type, suede type, etc. can be used. Suede type polishing pads (typically polyurethane polishing pads) are excellent in processability and are easy to realize high quality of the substrate surface. Note that the polishing pad used in the technology disclosed herein does not contain abrasive grains.
[0104] The suede-type polishing pad may be a buff pad, or may be a polishing pad in a non-buffed state where the surface is not buffed (so-called non-buff pad). Here, "buffing" refers to a process of roughly cutting the surface using a grindstone or the like, and typically refers to a process of removing the surface layer of the polishing pad to adjust the pore opening diameter and opening ratio.
[0105] Although not particularly limited, when a non-buff pad is used as the polishing pad, a pad dressing process and a dummy polishing process may be performed before polishing the substrate to be polished (object to be polished) to adjust the polishing surface of the polishing pad to a desired state. Here, the pad dressing process is a process of scraping off the surface layer of the polishing pad using a pad conditioner (pad dresser), and pores and fuzzed parts may exist on the surface of the polishing pad after the process. By performing polishing using a dummy substrate (typically a substrate of the same type as the substrate to be polished) on the polishing pad with such a surface, the surface state of the polishing pad after the pad dressing process is adjusted to a state suitable for subsequent polishing of the substrate to be polished. On the other hand, the polishing pad with the surface state thus adjusted has a smooth pad surface compared to a buff pad, and the pore diameter is also small (for example, about 20 μm), so that it is easy to adsorb to the substrate to be polished. Therefore, the polishing resistance between the substrate and the polishing pad tends to be high when using such a polishing pad. When polishing a substrate to be polished (Ni-P substrate) using such a polishing pad (typically a non-buff pad), the polishing resistance reduction effect achieved by using the polishing composition disclosed herein can be effectively exerted.
[0106] In the polishing method disclosed herein, the object to be polished is set in a polishing device while being held by a carrier, and polishing is performed. The carrier holds the side of the substrate to be polished during polishing, and is not particularly limited, but is usually a member having a holding hole called a hole, and the object to be polished is placed in the holding hole and polished.
[0107] The material of the carrier is not particularly limited, and for example, a resin material such as aramid resin or polycarbonate resin, a composite resin material such as fiber reinforced plastic (FRP), or a composite material combining these may be used. An example of such a composite material is a carrier made of an aramid laminate in which an aramid nonwoven fabric is impregnated with an epoxy resin. The technology disclosed herein is suitable for an embodiment in which a resin carrier such as an aramid resin is used. In an embodiment in which a resin carrier is used, the polishing resistance reduction effect of the technology disclosed herein can prevent or suppress deformation of the carrier caused by the polishing resistance.
[0108] Moreover, the carrier is usually configured to be thinner than the object to be polished. The thickness of the carrier is not limited to a specific range and is appropriately determined according to the object to be polished. The thickness of the carrier is, for example, 1.5 mm or less, usually 1 mm or less, and may be about 0.7 mm or less, or may be about 0.5 mm or less. A carrier having such a thickness is easily deformed when the load applied during polishing increases, but by applying the technology disclosed herein, the polishing resistance is reduced, the load applied to the carrier is alleviated, and deformation due to the load can be prevented or suppressed. The lower limit of the thickness of the carrier can be about 0.1 mm or more (for example, 0.2 mm or more).
[0109] After the object to be polished is polished as described above, the object to be polished is washed. For example, an alkaline washing step is carried out in which the object to be polished is washed with an alkaline washing liquid. The alkaline washing step includes, for example, contacting at least the surface of the object to be polished with an alkaline washing liquid. For example, the object to be polished can be brought into contact with the alkaline washing liquid by immersing the object to be polished in the alkaline washing liquid. An ultrasonic treatment may be carried out in which ultrasonic waves are applied to the object to be polished immersed in the alkaline washing liquid. In addition to or instead of applying ultrasonic waves, scrubbing may be carried out using a polyvinyl alcohol sponge, a nonwoven fabric, a nylon brush, or the like. The pH of the alkaline cleaning solution used in the alkaline cleaning step may be, for example, 7.5 or more, and from the viewpoint of improving cleaning properties, it is preferably 8.0 or more, more preferably 8.5 or more, for example 8.8 or more. In addition, from the viewpoint of preventing roughening of the substrate surface due to cleaning, the pH of the alkaline cleaning solution is suitably 11 or less, preferably 10 or less, and more preferably 9.5 or less. As the alkaline cleaning solution, an aqueous solution containing one or more of the above-mentioned basic compounds can be used. Among them, an aqueous solution of an alkali metal hydroxide is preferred, and for example, an aqueous solution of potassium hydroxide can be preferably used. The alkaline cleaning step may be performed using a commercially available alkaline cleaning solution.
[0110] After the polishing using the polishing liquid is completed, the object to be polished may be washed with a non-alkaline rinse liquid before proceeding to the alkaline washing step. The rinse liquid may be water such as pure water or ion-exchanged water, or an acidic aqueous solution (e.g., an aqueous solution with a composition obtained by removing abrasive grains from the polishing liquid).
[0111] <Application> The polishing composition disclosed herein is used for polishing a magnetic disk substrate (Ni-P substrate) plated with nickel phosphorus. The Ni-P substrate is a magnetic disk substrate having a nickel phosphorus plating layer on the surface of the substrate. The material of the substrate may be, for example, an aluminum alloy, glass, glassy carbon, etc. The polishing composition disclosed herein may be preferably used for polishing a Ni-P substrate having a nickel phosphorus plating layer on an aluminum alloy substrate. According to this specification, there can be provided a method for producing a Ni-P substrate, which includes a polishing step using the polishing composition disclosed herein and an alkaline cleaning step performed after the polishing step, and a Ni-P substrate produced by this method.
[0112] The polishing composition disclosed herein can be particularly preferably used in the final polishing step (finish polishing step) of Ni-P substrates. According to this specification, a method for producing a Ni-P substrate, which includes a final polishing step using the polishing composition disclosed herein and an alkaline washing step performed after the final polishing step, and a Ni-P substrate produced by the method can be provided. Note that the final polishing step refers to the last polishing step in the manufacturing process of the target object (i.e., a step after which no further polishing is performed). The manufacturing method of the substrate can further include a rough polishing step or a preliminary polishing step performed before the polishing step.
[0113] The polishing composition disclosed herein may be used in a polishing step upstream of the final polishing. Here, the polishing step upstream of the final polishing refers to a preliminary polishing step between the rough polishing step and the final polishing step. The preliminary polishing step includes at least a first polishing step, and may further include a second, third, etc. polishing step. The above-mentioned polishing composition can be used in any of the polishing steps, and the same or different polishing compositions can be used in these polishing steps. The polishing composition disclosed herein may be used, for example, in a polishing step performed immediately before the final polishing.
[0114] The polishing composition disclosed herein can be preferably used, for example, for polishing Ni-P substrates adjusted to a surface roughness of 20 Å or less by an upstream process. Here, the surface roughness refers to the surface roughness (arithmetic mean roughness (Ra)) measured by a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System. It is particularly preferable to apply the composition to polishing Ni-P substrates adjusted to a surface roughness of 10 Å or less. This allows Ni-P substrates with high quality surfaces to be produced with good productivity.
[0115] The matters disclosed in this specification include the following. [1] A polishing composition used for polishing a magnetic disk substrate having a nickel-phosphorus plating layer, comprising: The method comprises the steps of: abrasive grains, an acid, an oxidizing agent, a water-soluble polymer (A), and water; the water-soluble polymer (A) comprises one or more monomer units (a) having an SP value of 12.5 or more and one or more monomer units (b) having an SP value of less than 12.5; The polishing composition, wherein the water-soluble polymer (A) has an SP value within the range of 11-17. [2] A polishing composition used for polishing a magnetic disk substrate having a nickel-phosphorus plating layer, comprising: The method comprises the steps of: abrasive grains, an acid, an oxidizing agent, a water-soluble polymer (A), and water; The water-soluble polymer (A) is a copolymer of two or more vinyl monomers, The polishing composition, wherein the vinyl monomer comprises at least one monomer selected from structures I and II. [ka] (In Structure I, R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a linear or branched alkyl or alkenyl group having 10 or less carbon atoms, or R2 and R3 are bonded to each other to form a cyclic structure.) [3] The polishing composition according to [2] above, wherein the vinyl monomer further contains a carboxylic acid group-containing monomer. [4] The water-soluble polymer (A) is a copolymer of two or more vinyl monomers, The polishing composition according to the above-mentioned [1], wherein the vinyl monomer comprises at least one monomer selected from structures I and II. [ka] (In Structure I, R1 is a hydrogen atom or a methyl group, and R2 and R3 are each independently a linear or branched alkyl or alkenyl group having 10 or less carbon atoms, or R2 and R3 are bonded to each other to form a cyclic structure.) [5] The polishing composition according to [4] above, wherein the vinyl monomer further contains a carboxylic acid group-containing monomer. [6] The polishing composition according to any one of the above [1] to [5], wherein the abrasive grains are silica grains. [7] The average silanol group density of the silica particles is 3.0 / nm 2 The polishing composition according to the above item [6], which is as follows: [8] The polishing composition according to any one of the above [1] to [7], wherein the abrasive grains have an average aspect ratio of 1.0 or more and 1.3 or less as determined by observation with a transmission electron microscope. [9] The polishing composition according to any one of the above [1] to [8], wherein the water-soluble polymer (A) has a weight average molecular weight of 8,000 or more and 50,000 or less.
[10] The polishing composition according to any one of the above [1] to [9], having a pH value within the range of 1 to 4.
[11] The polishing composition according to any one of the above [1] to
[10] , which is used in a finish polishing step.
[12] A method for producing a magnetic disk substrate, comprising a step of polishing a substrate to be polished with the polishing composition according to any one of the above [1] to
[11] . EXAMPLES
[0116] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0117] <Material> Abrasive grain: Colloidal silica (50% cumulative diameter (D) in the particle size distribution based on the number of pieces based on TEM observation) 50 ): 25 nm, average aspect ratio based on TEM observation: 1.18, silanol group density: 1.6 / nm 2 ) Acid: Phosphoric acid (orthophosphoric acid) Oxidizing agent: Hydrogen peroxide Water-soluble polymers: as shown in Table 2. Chelating agent: L-glutamic acid diacetate·tetrasodium (GLDA·4Na) or 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP) Additive: naphthalenesulfonic acid formaldehyde condensate sodium salt or POE alkyl ether phosphate having Mw of 6000. In Table 3, "POE(n) alkyl(Cm) ether phosphate" means the number of oxyethylene units, and m means the number of carbon atoms in the alkyl group.
[0118] [Table 2]
[0119] The abbreviations for the monomers in Table 2 are as follows. AA: Acrylic acid MA: methacrylic acid ATBS: 2-acrylamido-2-methylpropanesulfonic acid AM: Acrylamide TBAA: N-tert-butylacrylamide DMAM: N,N-Dimethylacrylamide DEAM: N,N-diethylacrylamide DPAM: N,N-dipropylacrylamide DBAM: N,N-dibutylacrylamide St: styrene
[0120] <Preparation of Polishing Composition> (Examples 1 to 2, 4 to 12) A polishing composition was prepared containing colloidal silica (3.5 wt%) as abrasive grains, acid (2.0 wt%), an oxidizing agent (0.6 wt%), a water-soluble polymer (A) (0.04 wt%), a chelating agent (0.3 wt%) and deionized water, and adjusted to a pH of 1.6 with potassium hydroxide.
[0121] Example 3 The polishing composition of this example was prepared by further adding 0.02% by weight of a naphthalenesulfonic acid formaldehyde condensate to the composition of Example 1.
[0122] (Comparative Examples 1 and 3) A polishing composition according to each example was prepared in the same manner as in Example 1 or 2, except that no water-soluble polymer was used.
[0123] Comparative Example 2 The polishing composition of this example was prepared in the same manner as in Comparative Example 1, except that no oxidizing agent was used.
[0124] (Comparative Examples 4 to 6) Polishing compositions according to each example were prepared in the same manner as in Example 1 or 2, except that the water-soluble polymer was changed.
[0125] (Comparative Examples 7 to 8) Polishing compositions according to each example were prepared in the same manner as in Comparative Example 1, except that POE alkyl ether phosphate was further added.
[0126] An overview of each example is shown in Table 3.
[0127] <Measurement of polishing resistance> (Ni-P substrate polishing) The polishing composition according to each example was used as it was in the polishing liquid, and the substrate to be polished was polished under the following conditions. The substrate to be polished was an aluminum substrate for hard disks (Ni-P substrate) with an electroless nickel phosphorus plating layer on the surface, which had been pre-polished so that the surface roughness (arithmetic mean roughness (Ra)) measured by a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System was 6 Å. The diameter of the above-mentioned object to be polished was 3.5 inches (a doughnut shape with an outer diameter of about 95 mm and an inner diameter of about 25 mm) and the thickness was 1.75 mm.
[0128] (polishing conditions) Polishing device: Fujikoshi Machinery Co., Ltd. product name "RDP-500" Polishing pad: Suede pad (FILWEL) Pad surface roughness (Ra) during polishing resistance evaluation: 0.6 to 0.75 μm (measured using a portable surface roughness measuring instrument "Handysurf Plus" manufactured by Tokyo Seimitsu Co., Ltd.) Polishing load: 140g / cm2 Polishing platen rotation speed: 35 rpm Head rotation speed: 35 rpm Polishing fluid supply rate: 40mL / min Polishing time: 300 seconds The substrate was fixed to a carrier (thickness 1.5 mm) attached to the head portion.
[0129] (polishing resistance) The polishing resistance between the substrate to be polished and the polishing pad during polishing using the polishing composition according to each example was obtained from the polishing apparatus. Specifically, the force Fx applied in the X-axis direction (horizontal direction) to the head holding the substrate to be polished was taken as the polishing resistance between the substrate to be polished and the polishing pad, and the average value of the force Fx during the 120 seconds from 180 seconds after the start of polishing to the end of polishing (300 seconds) was measured as the polishing resistance. The obtained value was then converted into a relative value with the value of Comparative Example 1 taken as 100, and shown in the "polishing resistance (relative value)" column in Table 3.
[0130] <Measurement of polishing rate> (Ni-P substrate polishing) The polishing composition according to each example was used as it was in the polishing liquid to polish the object under the following conditions. The object to be polished was an aluminum substrate for hard disks having an electroless nickel phosphorus plating layer on its surface, which had been pre-polished so that the surface roughness (arithmetic mean roughness (Ra)) measured by a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System was 6 Å. The diameter of the object to be polished was 3.5 inches (a doughnut shape with an outer diameter of about 95 mm and an inner diameter of about 25 mm) and the thickness was 1.27 mm.
[0131] (polishing conditions) Polishing equipment: SpeedFam double-sided polishing machine, model "9B-5P" Polishing pad: Suede pad (FILWEL) Number of substrates to be polished: 10 ((2 substrates / carrier) x 5 carriers x 1 batch) Polishing fluid supply rate: 56mL / min Polishing load: 140g / cm 2 Lower surface plate rotation speed: 31rpm Polishing time: 300 seconds
[0132] (Washing) The polished Ni-P substrate was immersed in pure water and ultrasonically treated at a frequency of 170 kHz, then immersed in an alkaline cleaning solution (a cleaning solution "CSC-102B" available from Speedfam, diluted 200 times by volume) and scrubbed with a polyvinyl alcohol sponge while applying ultrasonic waves at a frequency of 170 kHz. The substrate was then immersed in pure water and ultrasonically treated at a frequency of 950 kHz, and then pulled out into an isopropyl alcohol atmosphere and dried.
[0133] (polishing rate) From the substrates obtained by polishing and cleaning with the polishing composition according to each example, randomly select 6 substrates (3 substrates / 1 batch), measure the weight loss of each substrate by polishing, calculate the polishing rate, and average the weight loss to obtain the polishing rate of each example.Specifically, the polishing rate is calculated based on the following formula: Polishing rate [μm / min] = weight loss of substrate due to polishing [g] / (substrate surface area [cm 2 ] × density of nickel phosphorus plating [g / cm 3 ] x polishing time [min] x 10 4 Here, the surface area of one side of the board is 66 cm 2 , the density of nickel phosphorus plating is 7.9g / cm 3 The obtained values were converted into relative values, with the value of Comparative Example 1 being set at 100, and shown in the column of "Polishing rate (relative value)" in Table 3.
[0134] [Table 3]
[0135] As shown in Table 3, in polishing a Ni-P substrate, in Examples 1 to 12, which used a polishing composition containing abrasive grains, acid, an oxidizing agent, and water, and further containing a copolymer consisting of a monomer unit (a) having an SP value of 12.5 or more and a monomer unit (b) having an SP value of less than 12.5 as the water-soluble polymer (A), the polishing resistance was reduced and the processability was improved compared to Comparative Examples 1 and 3, which did not use the water-soluble polymer. In Example 3, in which a naphthalenesulfonic acid formaldehyde condensate was further added to the composition of Example 1, a more excellent polishing resistance reduction effect was obtained. On the other hand, in Comparative Example 2, in which the oxidizing agent was not used in the composition of Comparative Example 1, the Ni-P substrate could not be polished (processing was not possible). In Comparative Example 4, in which polyacrylic acid not containing a monomer unit (b) having an SP value of less than 12.5 was used as the water-soluble polymer, the polishing resistance was reduced, but the processability could not be improved. In Comparative Examples 5 and 6, in which a copolymer not containing a monomer unit (b) having an SP value of less than 12.5 was used as a water-soluble polymer, the polishing resistance and processability were comparable to those of Comparative Examples 1 and 3, in which a water-soluble polymer was not used. In Comparative Examples 7 and 8, in which a water-soluble polymer was not used and POE alkyl ether phosphate was used as an additive, the polishing resistance could be reduced, but the processability also decreased. In addition, the polishing resistance and polishing rate were evaluated using a polishing composition prepared in the same manner as in Example 1, except that the concentration of the water-soluble polymer was changed to 0.02% by weight and 0.08% by weight, and it was confirmed that the results were comparable to those of Example 1.
[0136] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.
Claims
1. A polishing composition used for polishing a magnetic disk substrate having a nickel-phosphorus plating layer, comprising: The method comprises the steps of: abrasive grains; an acid; an oxidizing agent; a water-soluble polymer (A); and water; the water-soluble polymer (A) comprises one or more monomer units (a) having an SP value of 12.5 or more and one or more monomer units (b) having an SP value of less than 12.5; The polishing composition, wherein the water-soluble polymer (A) has an SP value within the range of 11 to 17.
2. The water-soluble polymer (A) is a copolymer of two or more vinyl monomers, The polishing composition according to claim 1 , wherein the vinyl monomer comprises at least one monomer selected from structures I and II. 【Chemistry 1】 (In structure I, R 1 is a hydrogen atom or a methyl group, R 2 , R 3 are each independently a linear or branched alkyl or alkenyl group having 10 or less carbon atoms, or R 2 , R 3 are bonded to each other to form a ring structure.)
3. The polishing composition according to claim 2 , wherein the vinyl monomer further comprises a carboxylic acid group-containing monomer.
4. The polishing composition according to claim 1, comprising silica particles as the abrasive grains.
5. The average silanol group density of the silica particles is 3.0 / nm 2 The polishing composition according to claim 4, wherein:
6. 4. The polishing composition according to claim 1, wherein the abrasive grains have an average aspect ratio of 1.0 or more and 1.3 or less as determined by observation with a transmission electron microscope.
7. 4. The polishing composition according to claim 1, wherein the water-soluble polymer (A) has a weight average molecular weight of 8,000 or more and 50,000 or less.
8. The polishing composition according to any one of claims 1 to 3, having a pH within the range of 1 to 4.
9. The polishing composition according to any one of claims 1 to 3, which is used in a finish polishing step.
10. 4. A method for producing a magnetic disk substrate, comprising a step of polishing a substrate to be polished with the polishing composition according to claim 1.
Citation Information
Patent Citations
Composition for polishing and manufacturing method of magnetic disk substrate
JP2022155732A